Glanders: A re-emerging dreaded disease of equids - Malik, Praveen; Singha, H; Singh, R. K. (Indian Farming, 2015)
Glanders is a zoonotic disease mainly affecting the equines, but it can also be transmitted to humans directly or indirectly by contact with food, water or equipments contaminated with discharges from affected animals. There is no proper treatment or vaccine available for glanders, therefore, its diagnosis, prevention and control are important.